Multibiomarker Responses of Juvenile Stages of Zebrafish (Danio rerio) to Subchronic Exposure to Polycyclic Musk Tonalide - Blahová, Jana; Divisova, Lenka; Plhalova, Lucie; Enevová, Vladimíra; Hostovsky, Martin; Doubková, Veronika; Marsalek, Petr; Fictum, Petr; Svobodova, Zdenka (Archives of environmental contamination and toxicology, 2018)
Synthetic polycyclic musks, widely used as additives in personal care products, are present in both biotic and abiotic matrices of the aquatic environment at concentrations of ng/l to µg/l. Although they are determined at comparatively low concentrations, these levels are biologically relevant and pose a significant growing risk as stressors to aquatic organisms. The purpose of our study was to evaluate the effects of 28-day-long exposure to polycyclic musk tonalide in zebrafish juvenile stages (Danio rerio) using selected biomarkers. Environmentally relevant concentrations of tonalide caused significant changes in selected enzyme activities in the experimental groups exposed to the highest concentrations. The activity of glutathione S-transferase and lipid peroxidation increased significantly (p < 0.05) after exposure to the highest concentration (50,000 ng/l) compared with the control. A similar trend was observed in catalase activity; there was a significant increase (p < 0.05) after exposure to two highest concentrations of tonalide (5000 and 50,000 ng/l). In addition, a statistically significant decrease (p < 0.05) in glutathione reductase activity was found in the lowest test concentration of tonalide (50 ng/l). None of the tested concentrations resulted in histopathological changes in liver, kidney, skin, or gill. Furthermore, no effects on body weight, body length, specific growth rate, and behavior were observed. Our results showed that tonalide exposure induced profound changes in the activities of antioxidant and detoxifying enzymes, such changes representing an adaptive response of the fish organism to tonalide toxicity.
Keywords: dánio pruhované; Animals; Environmental Biomarkers; katalasa; Antioxidants; Gills; oxidační stres; chemické látky znečišťující vodu; Catalase; Water Pollutants, Chemical; bioindikátory; Oxidative Stress; chování zvířat; glutathiontransferasa; testy subchronické toxicity; žábry; Glutathione Transferase; peroxidace lipidů; Zebrafish; tělesná hmotnost; Lipid Peroxidation; tetrahydronaftaleny; antioxidancia; Behavior, Animal; Body Weight; Toxicity Tests, Subchronic; zvířata; Tetrahydronaphthalenes